Comparative effectiveness of 10-week equipment-based pilates and diaphragmatic breathing exercise on heart rate variability and pulmonary function in young adult healthy women with normal BMI - a quasi-experimental study - Songül Adıgüzel; Dicle Aras; Mehmet Gülü; Monira I. Aldhahi; Abdulfattah S. Alqahtani; Sameer Badri AL-Mhanna (BMC, 2023)
Abstract Background The positive effects of Pilates and slow-controlled breathing exercises on health are examined in different studies. The purpose of the study was to investigate the effects of 10-week equipment-based Pilates, slow-controlled breathing exercises, and a combination of both on heart rate variability (HRV), pulmonary function, and body composition (BC) in young adult healthy women with normal BMI. Methods Forty female participants were assigned to either equipment-based Pilates group (PG), slow-controlled breathing exercise group (BG), equipment-based Pilates + breathing exercise group (PBG), and control groups (CG). Equipment-based Pilates exercise consists of training for two days a week and 50 min per day, and breathing exercises were done twice a week for 15 min a day for 8 weeks. In addition, PBG performed a 15-minute breathing exercise after each Pilates session. Pilates sessions were created with Reformer, Cadillac, Ladder Barrel, Chair Barrel, and Spine Corrector. On the other hand, breathing exercises were based on a controlled 5 s inhale and 5 s exhale cycles. Results Before and after the implementation, pulmonary function, HRV, and BC parameters were measured. The body weight and BMI improved in PG and PBG, and the percent body fat decreased only in PBG (p < 0.05). Both PG and PBG noted significant changes in HRV indices SDSD, SDNN, TP, HF, and LF. However, the RMSSD was recorded higher in only PBG. Similar changes were found in pulmonary parameters. The FVC, FEV1, VC, IC, TV, MVV, and VE im-proved in PBG. PG showed increases in VC and TV. The only changes found in BG were PEF and ERV. Conclusions The finding highlights the ample effect of combined breathing and Pilates exercise on HRV, pulmonary function and body composition which has important implications for health promotion.